2011
DOI: 10.1038/bjc.2011.463
|View full text |Cite
|
Sign up to set email alerts
|

Renal cancer and pneumothorax risk in Birt–Hogg–Dubé syndrome; an analysis of 115 FLCN mutation carriers from 35 BHD families

Abstract: Background:Birt–Hogg–Dubé (BHD) syndrome is an autosomal dominant condition caused by germline FLCN mutations, and characterised by fibrofolliculomas, pneumothorax and renal cancer. The renal cancer risk, cancer phenotype and pneumothorax risk of BHD have not yet been fully clarified. The main focus of this study was to assess the risk of renal cancer, the histological subtypes of renal tumours and the pneumothorax risk in BHD.Methods:In this study we present the clinical data of 115 FLCN mutation carriers fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
125
4
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(149 citation statements)
references
References 27 publications
(50 reference statements)
16
125
4
4
Order By: Relevance
“…Pneumothorax was observed in 5 out of 17 (29.4%) members who carried a mutation in this family, which was similar to a prevalence of 29% in a previous report (21). However, according to Jodie et al, the bullous lung changes observed on chest CT scan should be considered as the pulmonary manifestation of this syndrome (15).…”
Section: Resultssupporting
confidence: 58%
“…Pneumothorax was observed in 5 out of 17 (29.4%) members who carried a mutation in this family, which was similar to a prevalence of 29% in a previous report (21). However, according to Jodie et al, the bullous lung changes observed on chest CT scan should be considered as the pulmonary manifestation of this syndrome (15).…”
Section: Resultssupporting
confidence: 58%
“…1B). Papillary RCC with oncocytic change, clear cell RCC with focal papillary structures, RCC with a mixture of eosinophilic and focal clear cells with tubulopapillary architecture, sarcomatoid RCC and unclassified RCC have been described [17,29,31,36,37]. The association with renal angiomyolipoma has also been reported [38,39].…”
Section: Microscopic Findingsmentioning
confidence: 89%
“…A variety of histological subtypes including hybrid oncocytic tumor, chromophobe RCC, oncocytoma, papillary RCC and clear cell RCC have been observed [9,17,19,20,22,30,[33][34][35]. Hybrid oncocytic tumors have both areas reminiscent of chromophobe RCC having a well-defined cell border, pyknotic nuclei and perinuclear halo and oncocytoma showing ill-defined cell borders, finely granular eosinophilic cytoplasm and round nuclei [18] (Fig.…”
Section: Microscopic Findingsmentioning
confidence: 99%
See 2 more Smart Citations